2011
DOI: 10.1002/tox.20676
|View full text |Cite
|
Sign up to set email alerts
|

PCB 9 exposure induces endothelial cell death while increasing intracellular calcium and ROS levels

Abstract: Cultured porcine endothelial cells were used to determine the effects of several congeners of polychlorinated biphenyls (PCBs) on cell viability and changes induced by these congeners on levels of intracellular calcium and reactive oxygen species (ROS). Cultured endothelial cells were prepared as a single suspension and run on flow cytometry. Cell viability, intracellular calcium, and ROS concentrations were simultaneously determined by using propidium iodide, Fluo-3, and dihydrorodamine, respectively. The con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…12 Free Ca 2þ leads to the dissipation of mitochondrial membrane potential (MMP) and apoptosis. [13][14][15][16] ROS generation is one of the first and basic responses of the cells toward any kind of endogenous or environmental stress. 17 ROS production and degradation involve fine equilibrium, and during toxic insult, the equilibrium shifts toward massive ROS production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Free Ca 2þ leads to the dissipation of mitochondrial membrane potential (MMP) and apoptosis. [13][14][15][16] ROS generation is one of the first and basic responses of the cells toward any kind of endogenous or environmental stress. 17 ROS production and degradation involve fine equilibrium, and during toxic insult, the equilibrium shifts toward massive ROS production.…”
Section: Introductionmentioning
confidence: 99%
“…12 Free Ca 2+ leads to the dissipation of mitochondrial membrane potential (MMP) and apoptosis. 13 16…”
Section: Introductionmentioning
confidence: 99%
“…They found that both congeners caused DNA damage as monitored by the comet assay, but that PCB 52 is significantly more potent. Both PCB 9 (2,5 dichlorobiphenyl) (28) and PCB 11 (29) generate reactive oxygen species, known to be a risk factor for cell damage and death. Ludewig et al (30) found that PCB 3 (4-monochlorobiphenyl) and/ or its metabolites increase mutations in rat liver.…”
Section: Cancermentioning
confidence: 99%
“…ROS levels are balanced at low to moderate concentrations by the antioxidant defense mechanisms under physiological conditions. However, cigarette smoking, toxicants, obesity, a highfat diet, and/or aging may lead to the disruption of this balance [9,10]. The severity of the consequences of this imbalance depends on a variety of factors, including the level and the location of ROS production, the efficacy of antioxidant systems, and the cellular targets of ROS [11].…”
Section: Introductionmentioning
confidence: 99%